Human wellbeing index based on Maqasid al-Shari’ah (the objectives of Islamic law) - Ahmad Sarkawi, Azila; Abdullah, Muhammad Faris; Abdullah, Alias; Khazani, Nur Amilin (IJABR Press, 2017)
A review on the existing human wellbeing and liveability indexes, worldwide and in Malaysia, reveals five common themes in which their indicators could be grouped in, namely (i) politics and governance, (ii) economics, (iii) social and culture, (iv) environment and (v) infrastructure. This is evident in international indexes such as the Global Liveability Index by Economist Intelligence Unit (EIU), the Quality of Living Index by Mercer and the Most Liveable City Index by Monocle. In Malaysian context, the same themes can be found in the Malaysian Wellbeing Index by the Economic Planning Unit, the Malaysian Family Wellbeing Index by the National Population and Family Development Board and the Malaysian Urban and Rural Networks on Sustainable Development by the Federal Town and Country Planning Department. However, it is contended that these indexes were not developed based on maqasidic approach. Thus, this study aims to examine the components enumerated under these indexes and consequently to map them against the five essentials of Maqasid al-Shari’ah, which are the preservation of faith, self, intellect, posterity and property. Content analysis on the related document is deployed and supported with extensive literature review. Finally the human wellbeing index with maqasidic approach is proposed.